Carcass and Cooked Meat Acceptance of Broilers Chickens Fed the Diet Containing Fermented Moringa with the Addition Corn and Fishmeal - zulfan zulfan; Cut Aida Fitri; Asmaul Husna; Nurganti Siapudan (Buletin Peternakan, 2023)
The purpose of this study was to evaluate the organoleptic acceptance on the carcass and cooked meat of broilers fed the diet containing the fermented moringa leaves and yellow corn with the addition of fish meal or none.This study used 100 broiler chicks strain MB 90 and a commercial diet CP511 Bravo (CD). The substitute feed ingredients were composted of fermented domesticated Moringa oleifera leaf(FDMOL), yellow corn (YC), rice bran (RB), top mix (TM), and local commercial fish meal (FM). The study was performed in a Completely Randomized Design (CRD) with subsampling consisting of 5 treatments, 4 replicates, and 2 subsamples. The experimental diets were C 1 = 100% CD, C 2 =84.5% CD + 7.5% YC + 7.5% RB + 0.5% TM, C 3 = 84.5% CD + 5% YC + 5% RB + 5% TM + 0.5% TM, MCR= 84.5% CD + 5%FDMOL + 5% YC + 5% RB + 0.5% TM (moringa+), and MCF= 84.5% CD + 5% FDMOL + 5% YC + 5% FM + 0.5% TM (moringa++). The results indicated that carcasses from broilers fed the moringa-base diets were significantly higher (P<0.05) yellow coloration than those fed the control diets but the panelists’ acceptances for carcass organoleptic either fresh or cooking were not significantly different (P>0.05). In conclusion, there were no impacts on the acceptance of fresh carcass characteristics(conformation, color, and odor) or cooked meat (color, flavor, and taste) from the broilers fed the diets containing the moringa leaves compared to the control.